Melanocytic colonization of a meningothelial meningioma: Histopathological and ultrastructural findings with immunohistochemical and genetic correlation: Case report - (:unkn) unknown (Lippincott Williams and Wilkins, 2003)
OBJECTIVE AND IMPORTANCE: Melanocytic colonization of nonpigmented extracranial tumors has been reported in adenocarcinomas, squamous cell carcinomas, skin appendage tumors, and dermatofibrosarcoma protuberans. To our knowledge, tended through the calvarium INTERVENTION: Craniotomy with gross total resection of the tumor was performed. Histochemistry, immunochemistry, ultrastructural analysis, and molecular genetic study via fluorescence in situ hybridization confirmed melanocytic colonization of a meningothelial meningioma. CONCLUSION: With the inclusion of meningothelial meningioma, the spectrum tumors affected by melanocytic colonization continues to expand.
Keywords: Bednář tumor; Fluorescence in situ hybridization; Melanin; Melanocytic colonization; Meningioma; Ultrastructure